2017
DOI: 10.1117/1.jbo.22.12.121711
|View full text |Cite
|
Sign up to set email alerts
|

Review of optical coherence tomography in oncology

Abstract: The application of optical coherence tomography (OCT) in the field of oncology has been prospering over the past decade. OCT imaging has been used to image a broad spectrum of malignancies, including those arising in the breast, brain, bladder, the gastrointestinal, respiratory, and reproductive tracts, the skin, and oral cavity, among others. OCT imaging has initially been applied for guiding biopsies, for intraoperatively evaluating tumor margins and lymph nodes, and for the early detection of small lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 194 publications
0
80
0
Order By: Relevance
“…In fact, the only way to make an accurate diagnosis of a non-invasive neoplasm would be to examine every serial section of every piece of tumor capsule at the cost of exhausting the tissue. This would be considered absurd but may in fact become possible as we learn to apply novel imaging technologies that can see through full blocks of tissue [3]. In the interim, we must balance the risk by identifying areas of suspicion and recognizing that we have a responsibility to cut multiple deeper sections to ensure that we have not missed a focus of true invasion.…”
mentioning
confidence: 99%
“…In fact, the only way to make an accurate diagnosis of a non-invasive neoplasm would be to examine every serial section of every piece of tumor capsule at the cost of exhausting the tissue. This would be considered absurd but may in fact become possible as we learn to apply novel imaging technologies that can see through full blocks of tissue [3]. In the interim, we must balance the risk by identifying areas of suspicion and recognizing that we have a responsibility to cut multiple deeper sections to ensure that we have not missed a focus of true invasion.…”
mentioning
confidence: 99%
“…Originally developed for ophthalmic applications to image the posterior segment of the eye [3,[33][34][35] and further enhanced with OCT angiography [36,37], OCT has found successful applications in the anterior segment of the eye [30], as well as in a number of fields, including dermatology [38,39], oncology [40][41][42][43][44][45][46] and dentistry [47]; in endoscopic form it has been applied to cardiology [48,49], gastroenterology [50,51], and pulmonology [52][53][54]. Numerous embodiments of functional OCT [55], including Doppler OCT and polarization-sensitive OCT [56,57], as well as optical coherence elastography [58][59][60][61][62][63][64], multimodal fluorescence-OCT [2,[65][66][67] and spectroscopic OCT [68], have been developed to enhance the structural information obtained with OCT with properties related to tissue function.…”
Section: Applicationsmentioning
confidence: 99%
“…Numerous ex vivo and in situ studies have reported that OCT is able to readily differentiate normal microstructure from neoplasia in several tissues (e.g., cervix, breast, thyroid, bladder, colon polyps, etc.). [6][7][8][9] High-speed OCT offers a novel method for real-time intraoperative evaluation of surgical margins. Whilst OCT is highly sensitive in identifying preinvasive and invasive cancer of the uterine cervix, 10 it…”
Section: Op T Ic Al Coh E Re Nc E T Om Ogr Ap H Ymentioning
confidence: 99%